A tale of three sisters - Fajardo, Anika; Escobar, Paola (Los Angeles : Disney Press, 2022)
Encanto tells the tale of an extraordinary family, the Madrigals, who live in a magical house in an enchanted town hidden in the mountains of Colombia. The magic of the Encanto has blessed every child in the family with a unique gift from super strength to the power to heal, that's every child except one, Mirabel. But when this ordinary child discovers that the magic surrounding the Encanto is in danger, she may be her family's last hope.
Keywords: Sisters -- Juvenile fiction; Families -- Juvenile fiction; Ability -- Juvenile fiction; Dwellings -- Juvenile fiction; Magic -- Juvenile fiction; Survival -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Colombia -- Juvenile fiction